Anti-hepatitis B surface (anti-HBs) seroprotection in children with acute lymphoblastic leukemia post hepatitis B vaccination in Indonesia - Roni Naning, Yustinah Nenny Sri Mulyani (Universitas Gadjah Mada, 2014)
Children with acute lymphoblastic leukemia (ALL) receiving chemotherapy are at high risk fordeveloping hepatitis B infection. Protective effect of hepatitis B vaccination in children withALL in Indonesia has not been investigated yet. The aim of study was to determine the proportiondifference of anti-HBs seroprotection between children with ALL and without malignancy posthepatitis B vaccination. We had conducted a case-control study from January to February 2012at Dr. Sardjito General Hospital, Yogyakarta. We ascertained 1-15 years old children with ALLreceiving chemotherapy and without malignancy who had hepatitis B vaccination. Sixty sevenchildren were included in this study. Anti-HBs seroprotection level was measured using anenzyme-linked immunosorbent assay (ELISA). The results were analyzed using Chi-square test.Twenty one children (65.6%) with ALL and 13 children (37.1%) without malignancy showedanti-HBs seroprotection. The difference was statistically significant with p-value of 0.020(prevalence ratio [PR]=0.3; 95% CI=0.11-0.84). Both groups showed no significantly differenceof anti-HBs seroprotection according to either female gender, risk classification, or phase ofchemotherapy with p-value of 0.38 (PR =4; 95% CI=1.05-15.2), 0.248 (PR =3.37; 95%CI=0.58-19.6) or 0.214, respectively. In conclusion, the proportion of anti-HBs seroprotectionin children with ALL is higher than those without malignancy.